Ultraconserved Elements in the Olig2 Promoter - Chen, Christina T. L. (Public Library of Science, 2008)
BACKGROUND: Oligodendrocytes are specialized cells of the nervous system that produce the myelin sheaths surrounding the axons of neurons. Myelinating the axons increases the speed of nerve conduction and demyelination contributes to the pathology of neurodegenerative diseases such as multiple sclerosis. Oligodendrocyte differentiation is specified early in development by the expression of the basic-helix-loop-helix transcription factor Olig2 in the ventral region of the neural tube. Understanding how Olig2 expression is controlled is therefore essential for elucidating the mechanisms governing oligodendrocyte differentiation. A method is needed to identify potential regulatory sequences in the long stretches of adjacent non-coding DNA that flank Olig2. METHODOLOGY/PRINCIPAL FINDINGS: We identified ten potential regulatory regions upstream of Olig2 based on a combination of bioinformatics metrics that included evolutionary conservation across multiple vertebrate genomes, the presence of potential transcription factor binding sites and the existence of ultraconserved elements. One of our computational predictions includes a region previously identified as the Olig2 basal promoter, suggesting that our criterion represented characteristics of known regulatory regions. In this study, we tested one candidate regulatory region for its ability to modulate the Olig2 basal promoter and found that it represses expression in undifferentiated embryonic stem cells. CONCLUSIONS/SIGNIFICANCE: The regulatory region we identified modifies the expression regulated by the Olig2 basal promoter in a manner consistent with our current understanding of Olig2 expression during oligodendrocyte differentiation. Our results support a model in which constitutive activation of Olig2 by its basal promoter is repressed in undifferentiated cells by upstream repressive elements until that repression is relieved during differentiation. We conclude that the potential regulatory elements presented in this study provide a good starting point for unraveling the cis-regulatory logic that governs Olig2 expression. Future studies of the functionality of the potential regulatory elements we present will help reveal the interactions that govern Olig2 expression during development.